2009
DOI: 10.1038/sj.bjc.6605113
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative immunohistochemical expression of c Kit in breast carcinomas is predictive of patients' outcome

Abstract: BACKGROUND: c Kit (CD117) expression in tissues has been reported as a relevant target for specific therapy in some human malignancies, but has been poorly documented in breast carcinomas METHODS: The prognostic significance of c Kit in a series of 924 breast carcinomas (mean follow-up, 79 months) was investigated using standardised high-throughput quantitative densitometry of immunohistochemical precipitates in tissue microarrays. RESULTS: c Kit was expressed in 14.7% breast carcinomas (and in 42 out of 586 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 25 publications
1
14
0
1
Order By: Relevance
“…Overexpression of c-Kit in tumors points to the presence of cancer stem cells and predicts treatment resistance and poor outcomes. Therefore, disruption of c-Kit expression in c-Kit-driven tumors represents a promising therapeutic approach [46], [47]. In this study we demonstrated that both Dox and AN-7 substantially reduce Ki-67 and c-Kit expression in the tumor and AN-7+Dox abolish it, supporting the notion that the combination treatment can potentially benefit treatment-resistance and aggressive tumors.…”
Section: Discussionsupporting
confidence: 70%
“…Overexpression of c-Kit in tumors points to the presence of cancer stem cells and predicts treatment resistance and poor outcomes. Therefore, disruption of c-Kit expression in c-Kit-driven tumors represents a promising therapeutic approach [46], [47]. In this study we demonstrated that both Dox and AN-7 substantially reduce Ki-67 and c-Kit expression in the tumor and AN-7+Dox abolish it, supporting the notion that the combination treatment can potentially benefit treatment-resistance and aggressive tumors.…”
Section: Discussionsupporting
confidence: 70%
“…Concerning c-kit expression and prognosis the available data are controversial. In a recent study by Charpin et al [28] c-Kit expression in patients with breast carcinomas correlated with a poor patient outcome while a other study found that a loss of the c-kit expression is associated with an advanced stage of breast cancer [32].…”
Section: Resultsmentioning
confidence: 98%
“…While numerous clinical studies showed that cancer patients with either over-expression and/or mutations of c-Kit in their clinical samples have significantly poor prognosis, lower survival rates and show resistance to chemotherapy [25][26][27][28][29][30] other studies found no prognostic significance of c-kit expression [31][32][33].…”
Section: Introductionmentioning
confidence: 98%
“…При цьому збільшувалася концентрація диференційованих CD44 + СD24 + -, CD44 -СD24 +та CD117 + -клітин порівняно з контролем. Деякими авторами підвищення рівня експресії CD117 вважається можливим тестом ефективності протипухлинної терапії [26]. У такому разі відзначене нами підвищення концентрації CD117 + -клітин удвічі порівняно з контролем на тлі пригнічення росту АКЕ на 58,24±3,45% може бути взаємозумовлюючим та свідчити про позитивний ефект цієї терапії (див.…”
Section: результати та їх обговоренняunclassified